IKLAN DAN M1TOS MODERNITAS - Hcsti Rahayu (Ars: Jurnal Seni Rupa dan Desain, 2008)
To become modem and prosperous is the dream o f all people, indeed every nation. However, it is noteasy, and it often does not fit with the facts. The advertisement is considered the most effective and efficientway to infuse the image o f modernity and prosperity.By applying Roland Barthes' theories on semiology, this paper invites the readers to pay close attentionand at the same time to be critical towards advertising as well as other visual phenomena in the mass media.An advertisement as purl o f visual communication design is supposed to be used as a means o f to formpositive awareness so that people won’t be trapped in the Dutch colonial system which used advertisingnot only to market the product but also to inject the idea (in a form o f a myth) o f national identity andmodernity through technology.Keywords: advertisement, myth, modernity